Agricultural Communications Students Describe a Short-term Field Experience - Angel N RIggs; Diane Montgomery (Journal of Applied Communications, 2018)
Student-run publications, including newsrooms and similar agency-style work achieve the curricular goal of experiential learning (Roberts, 2006) for university agricultural communication students. Gaining a journalistic skillset in the classroom is richly supplemented with experiencing real-world and authentic agency immersion to reveal to students the genuine characteristics of a workplace. The purpose of this study was to use Q methodology to evaluate a real-world, out-of-class-but-supervised newsroom producing publications for the State FFA Convention. Fifteen undergraduate students who were immersed in this three-day program in which students publish original work to disseminate information to FFA participants and the public participated in the study at the end of the newsroom experience. With a concourse sampled along four dimensions of growth and development (Author, 2014), a Q set of 36 statements was sorted. In addition to the Q sorts, comments gathered from the students at the last session assisted in the interpretation of data. Post-sort interviews were conducted with exemplar sorters. Data were analyzed using principal components and varimax rotation and interpreted to show three ways the newsroom was experienced by the university students. The Supervisors honed managerial skills while working as colleagues with faculty supervisors. The Contented Staff valued the education gained from the experience and recognized the practical application of the communications-based skill-set. The Stressed Staff had insecurities and physical discomfort during the work and living in the city. Implications for program development, classroom instruction, and field experience assessment will be discussed.
Keywords: Q Methodology; Short-term Field Experience; Student Newsroom